1998
DOI: 10.1128/aem.64.2.575-580.1998
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Broad-Host-Range Lytic Bacteriophages of Sphaerotilus natans , Escherichia coli , and Pseudomonas aeruginosa

Abstract: Two bacteriophage collections were examined with regard to their ability to form plaques on multiple bacterial host species. Nine of 10 phages studied were found to be broad-host-range bacteriophages. These phages fell into two groups. Group 1, the SN series, was isolated from sewage treatment plant samples with Sphaerotilus natansATCC 13338 as a host. The DNAs of these bacteriophages contained modified bases and were insensitive to cleavage by type I and II restriction endonucleases. The efficiency of plating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
121
1
8

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(134 citation statements)
references
References 34 publications
2
121
1
8
Order By: Relevance
“…There are a number of indications that aquatic viruses can have a broad host-range, furthermore broad-host range (polyvalent) bacteriophages have been isolated from aquatic environments (Moebus and Nattkemper, 1981;Jensen et al, 1998;Wichels et al, 1998;Sano et al, 2004). It is likely that polar freshwater viral communities are composed of both host-specific and polyvalent phages.…”
Section: Resultsmentioning
confidence: 99%
“…There are a number of indications that aquatic viruses can have a broad host-range, furthermore broad-host range (polyvalent) bacteriophages have been isolated from aquatic environments (Moebus and Nattkemper, 1981;Jensen et al, 1998;Wichels et al, 1998;Sano et al, 2004). It is likely that polar freshwater viral communities are composed of both host-specific and polyvalent phages.…”
Section: Resultsmentioning
confidence: 99%
“…Phage-bacterial networks can be used to predict which phages may be useful against pathogenic bacteria, while also preventing loss of beneficial mutualist bacteria. Questions about the host range of bacteriophage have been asked for some time (Frisch and Levine, 1936) and phages have been shown to have both narrow and broad host range (Yarmolinsky and Sternberg, 1998;Jensen et al, 1998;Holmfeldt et al, 2007;Flores et al, 2011;Weitz and Wilhelm, 2012;Flores et al, 2012) while similarly, bacteria are commonly susceptible to multiple phage strains, which can be evolutionary and/or geographical distant (Flores et al, 2012).…”
Section: Theoretical Use Of Network To Predict Candidates For Phage mentioning
confidence: 99%
“…A wild-type bacteriophage Sn-T, isolated from the sheathed bacterium Sphaerotilus natans, is able to infect members of Enterobacteriaceae, phototrophic bacteria and the Pseudomonadaceae. It can also mediate transduction in Pseudomonas and presumably other members of the above families [22]. Even so, of the three DNA exchange methods, the barriers to foreign DNA entry are strongest for transduction.…”
Section: Dna Entrymentioning
confidence: 99%
“…However, many phages carry their own defenses against restric-tion including : inactivation of host endonuclease or methylase (phage T3, see [33]), or self-methylation [34]. Jensen et al [22] found that a large fraction of broad-host-range phage isolated from the environment were resistant to type I and type II restriction endonucleases, most likely due to modi¢cation of viral DNA. Finally, it is not clear as to what the fate of the DNA transduced by the phage is.…”
Section: Restriction Enzymesmentioning
confidence: 99%